2021
DOI: 10.1186/s12882-021-02307-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic kidney disease and the most common corneal ectasia disease (keratoconus): a nationwide cohort study

Abstract: Background Both keratoconus (KCN) and chronic kidney disease (CKD) are multifactorial conditions with multiple aetiologies and share several common pathophysiologies. However, the few studies that have described the relationship between KCN and CKD are limited to case reports and small case series. This study aimed to evaluate the association between KCN and CKD. Methods The study cohort included 4,609 new-onset keratoconus patients ≥ 12 years iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The patient in this case has a history of chronic kidney disease (CKD) and keratoconus. As there was not a full history available, we do not know when these conditions were diagnosed but, interestingly, a recent study in 2021 discovered a link between them and found that male patients with keratoconus are 1.36 times more likely to be diagnosed with CKD [4]. Wong et al [5] also suggest an association between CKD and glaucoma, cataract, macular degeneration, and ocular surface disease and suggest that further understating of this may enable development of future treatments for both kidney and ocular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in this case has a history of chronic kidney disease (CKD) and keratoconus. As there was not a full history available, we do not know when these conditions were diagnosed but, interestingly, a recent study in 2021 discovered a link between them and found that male patients with keratoconus are 1.36 times more likely to be diagnosed with CKD [4]. Wong et al [5] also suggest an association between CKD and glaucoma, cataract, macular degeneration, and ocular surface disease and suggest that further understating of this may enable development of future treatments for both kidney and ocular disease.…”
Section: Discussionmentioning
confidence: 99%